Synthesis, structure and multicolor-tunable luminescence of the dandelion-like SiO2:Ln3+ (Ln = Eu, Tb) nanophosphors. (5th June 2017) - Xie, Xiaoming; Chen, Jie; Sheng, Ye; Song, Yanhua; Zhou, Xiuqing; Zhang, Xiangting; Shi, Zhan; Zou, Haifeng; Zheng, Keyan
Abstract : Dandelion-like SiO2 :Ln 3+ (Ln = Eu, Tb) nanophosphors of 70 nm diameter have been synthesized, and colorful emission phosphors were obtained by Ln 3+ doping. Abstract : A series of novel color tunable dandelion-like SiO2 :Ln 3+ (Ln = Eu, Tb) nanophosphors of approximately 70 nm diameter were prepared using a simple hydrothermal route. The phase, time-dependent shape evolution, morphology, sizes, and luminescence properties of the as-prepared products were well characterized by means of X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray spectrometry, and photoluminescence spectra as well as kinetic decay curves. Under ultraviolet excitation, the Eu 3+ and Tb 3+ singly doped SiO2 samples showed strong red and green emission, respectively. Furthermore, the luminescence colors of the as-prepared Tb 3+, Eu 3+ co-doped dandelion-like SiO2 nanophosphors could be altered from green to red, including green-yellow, yellow, orange yellow and reddish orange, by simply adjusting the doping concentrations of Eu 3+ .